Serum selenoprotein P, but not selenium, predicts future hyperglycemia in a general Japanese population. Issue 1 (December 2018) - Oo, Swe; Misu, Hirofumi; Saito, Yoshiro; Tanaka, Mutsumi; Kato, Seiji; Kita, Yuki; Takayama, Hiroaki; Takeshita, Yumie; Kanamori, Takehiro; Nagano, Toru; Nakagen, Masatoshi; Urabe, Takeshi; et al.
Abstract We aimed to test the hypothesis that selenoprotein P (SELENOP), a hepatokine involved in the development of both insulin resistance and impaired insulin production in mice, is related to future onset of hyperglycemia in humans. 76 healthy non-pregnant human subjects without diabetes underwent oral glucose tolerance test (OGTT) at baseline and 4-years follow-up. Nine subjects developed either impaired glucose tolerance or type 2 diabetes at follow-up. At baseline, SELENOP concentrations correlated negatively with insulinogenic index, but not with homeostasis model assessment-estimated insulin resistance (HOMA-IR). Multivariate analysis showed that baseline SELENOP predicted fasting plasma glucose at follow-up independently of the other parameters. The receiver operating characteristic (ROC) curve analysis showed that baseline concentrations of serum SELENOP, but not of selenium, were a reliable test to predict future onset of glucose intolerance. In conclusion, elevation of circulating SELENOP, but not of circulating selenium, was positively and independently associated with future onset of glucose intolerance in a general Japanese population.